Flood durations of the year 2023 on the floodplains of River Rhine and River Elbe, Germany - Weber, Arnd (PANGAEA, 2024)
Floodplains are morphologically highly heterogeneous environments with dynamically in- and decreasing water levels and flows. Strong environmental filtering through floodplain inundation creates favorable conditions for highly specialized organisms leading to high biodiversity and conservation value of floodplains. With hyd1d and hydflood we provide two R packages for simplified hydrologic modelling in two large central European floodplains – along River Rhine and River Elbe in Germany. We applied the R function hydflood::flood3 on both active floodplains covering the year 2023. The datasets consists of 40 tiles along River Rhine and 49 tiles along River Elbe, resulting in a total of 89 individual raster datasets stored in GeoTiff file format. All raster have a spatial resolution of 1 m and are stored in the coordinate reference systems ETRS 1989 UTM Zone 32 N (EPSG: 25832) for River Rhine and ETRS 1989 UTM Zone 33 N (EPSG: 25833) for River Elbe.
Keywords: Flood duration; Flood inundation; floodplain; River Elbe; River Rhine